Loss of FAM83H promotes cell migration and invasion in cutaneous squamous cell carcinoma via impaired keratin distribution. Issue 2 (November 2021) - Tokuchi, Keiko; Kitamura, Shinya; Maeda, Takuya; Watanabe, Masashi; Hatakeyama, Shigetsugu; Kano, Satoshi; Tanaka, Shinya; Ujiie, Hideyuki; Yanagi, Teruki
Highlights: Loss of FAM83H in cutaneous Squamous cell carcinoma. Loss of FAM83H enhances cell migration and invasion in cutaneous SCC. FAM83H forms a complex with TRIM29 and keratins . FAM83H regulates keratin distribution and solubility. Loss of FAM83H is associated with altered keratin distribution in clinical samples. Abstract: Backgrounds: FAM83H is essential for amelogenesis, but recent reports implicate that FAM83H is involved in the tumorigenesis. We previously clarified that TRIM29 binds to FAM83H to regulate keratin distribution and squamous cell migration. However, little is known about FAM83H in normal/malignant skin keratinocytes. Objective: To investigate the expression of FAM83H in cutaneous squamous cell carcinoma (SCC) and its physiological function. Methods: Immunohistochemical analysis and RT-PCR of human SCC tissues were performed. Next, we examined the effect of FAM83H knockdown/overexpression in SCC cell lines using cell proliferation, migration, and invasion assay. To investigate the molecular mechanism, immunoprecipitation of FAM83H was examined. Further, Immunoﬂuorescence staining was performed. Finally, we examined the correlation between the expressions of FAM83H and the keratin distribution. Results: FAM83H expression was lower in SCC lesions than in normal epidermis and correlated with differentiation grade. The mRNA expression levels of FAM83H in SCC tumors were also lower than in normal epidermis. The knockdown of FAM83H enhanced SCC cell migration and invasion, whereas the overexpression of FAM83H led to decreases in both. Furthermore, the knockdown of FAM83H enhanced the cancer cell metastasis in vivo . FAM83H formed a complex with TRIM29 and keratins. The knockdown of FAM83H altered keratin distribution and solubility. Clinically, the loss of FAM83H correlates with an altered keratin distribution. Conclusion: Our findings reveal a critical function for FAM83H in regulating keratin distribution, as well as in the migration/invasion of cutaneous SCC, suggesting that FAM83H could be a crucial molecule in the tumorigenesis of cutaneous SCC.